Crises and confidence: Systemic banking crises and depositor behavior - Osili, Una Okonkwo; Paulson, Anna (Journal of Financial Economics, 2014)
We show that individuals who have experienced a systemic banking crisis are 11 percentage points less likely to use banks in the U.S. than otherwise similar individuals who emigrated from the same country but did not live through a crisis. This finding is robust to controlling for exposure to other macroeconomic events and to various methods for addressing potential bias due to migrant self-selection. Consistent with the view that personal experience plays an important role in decision-making, the effects are larger for individuals who were older and more likely to have had wealth entrusted to the banking system at the time of the crisis and for people who experienced crises in countries without deposit insurance.